Decentralized service delivery in Nairobi and Mombasa: Policies, politics and inter-governmental relations - Winnie V. Mitullah (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
In many African countries, decentralization has long been viewed as a means for improving local service delivery. Yet, despite various decentralization initiatives, poor service delivery continues to be problematic in two of Kenya's largest cities, Nairobi and Mombasa. Despite various governance reforms to enhance Kenya's decentralization process, backed up by constitutional provisions and legislation, this study highlights that a proliferation of actors with overlapping mandates, opaque development frameworks, and intra- and inter-party politics remain major obstacles to providing critical services in these two cities. It is concluded that the effective decentralization of service delivery in cities cannot occur without key accompanying policies, including the devolution of resources and amicable inter-governmental relations.
Keywords: D72; H70; N47; O18; 330; decentralization; development aid; inter-governmental relations; politics; service delivery